Diatoms (Bacillariophyceae) associated with free-drifting Antarctic icebergs: taxonomy and distribution - Cefarelli, Adrián Oscar; Ferrario, Martha Elba; Vernet, María (Polar Biology)
There are several recent studies about life in relation to Antarctic icebergs. Diatom communities have been found living on submerged vertical walls of icebergs. In this study we complement and extend the taxonomic and ecological information on diatoms associated with icebergs. Two expeditions were carried out during winter 2008 and fall 2009. Samples were collected in situ from Antarctic icebergs and in adjacent waters, with a remote operated vehicle and with a mesh net, respectively, and subsequently analyzed using light and electron microscopy. Thalassioneis signyensis, dominant species growing on the icebergs? flanks, provided substrate for other diatoms, mainly Synedropsis lata var. angustata, S. recta, Fragilaria cf. islandica var. adeliae, Attheya gaussii, Navicula cf. perminuta, Amphora sp. and Nitzschia spp. New morphological and ecological characteristics are given for S. lata var. angustata, S. recta and A. gaussii. We report also Biddulphia alternans and Coscinodiscus concinnus for the first time in Antarctic waters. Similar to sea ice algae, the term sympagic is used to describe the habitat of these diatom communities. Taxa uncommon to marine plankton, either benthic, epiphytic or freshwater forms, occurred in waters under icebergs? influence: Amphora sp., B. alternans, Cocconeis spp., Delphineis minutissima, Licmophora gracilis, Luticola cf. australomutica, Opephora sp., Pinnularia spp., Plagiogramma sp., Psammodictyon panduriforme var. minor, Pseudogomphonema kamtschaticum, Rhaphoneis amphiceros, S. recta and T. signyensis. Our results support the hypothesis that species associated with icebergs exchange between several habitats: coastal, benthos, plankton, periphyton, ice shelves, icebergs and sea ice, making icebergs acting as a physical agents to transport and distribute organisms in between these habitats. Fil: Cefarelli, Adrián Oscar. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. División Ficología; Argentina. Consejo Nacional de Investigaciones Científicas y ...